Implementation of PID control Based Hybrid Model for Gesture Controlled Robotic Arm - Pratihar, Raktim; Sadhukhan, Debmalya; Bhowmick, Roberto; Mullik, Anuron; Majumder, Bansari Deb (International Journal of Computer Sciences and Engineering, 2020)
Human beings have been developing and designing since the stone age. They have worked for the betterment of society ever since. However, it is always not possible for them to attend a situation at a given time in person. Hence, the solution we came up with is a gesture-controlled robotic arm where we are controlling the device from a distant location. The project comprises mainly of two parts, viz, the sending and receiving part. In the sending part, we are using an MPU6050 3- axis gyroscope plus a 3-axis accelerometer sensor compiled with an Arduino nano micro-controller and an IR transmitter based bend sensor is used. Similarly, for transferring information, we are using an RF module. In another part. The thing that is happening in the robotic arm moves up, down, left, or right along with gripping according to the hand movement made by the user. Following the direction of the movement, the gripping process is brought about. The applications of this project can be found in the fields of biomedical, defense, industrial, and many others. Like in the medical field, during times of surgery, the doctors can carry out the operation even in his absence at that particular location. Also, in the field of defense, our robotic arm can be of great importance, like diffusing a bomb without the intervention of humans. Thus, in this era of science and technology, where the world says nothing is impossible, few factors provide limitations to this. So, by using this project, we tried to give a hand to reduce the problems of society